Factors Associated with the Incidence of Hypertension at the Olak Kemang Health Center, Danau Teluk District, Jambi City - Yunicha Anggraini; Rd. Halim (PT FORMOSA CENDEKIA GLOBAL, 2023)
The World Health Organization (WHO) states ± 1.28 billion individuals worldwide suffer from hypertension. This study aims to determine the factors associated with the incidence of hypertension. This study used a cross-sectional design. The results of bivariate analysis showed that there was no relationship between age (p=0.454), gender (p=0.665), obesity status (p=0,154) and smoking status (p=0.520) with hypertension. There was a relationship between family history (p=0.004), physical activity (p=0,008) and consumption of fatty foods (p=0.000) with hypertension. Conclusion: Variables related to the incidence of hypertension at the Olak Kemang Public Health Center, Danau Teluk Teluk District, Jambi City, were family history, physical activity and consumption of fatty foods. It is recommended for the public to regularly check blood pressure and avoid risk factors that can cause hypertension.